2016
DOI: 10.18178/joaat.3.4.258-264
|View full text |Cite
|
Sign up to set email alerts
|

Drying Characteristics of Crackers from Sorghum Using Tray Dryer in Different Drying Air Velocities

Abstract: A tray dryer using source of energy from biomass and solar was developed to dry sorghum crackers. In this dryer, solar dryer was combined with a heating system of drying air through pipes above the furnace while cooking sorghum stem's juice. This research investigated drying characteristics of sorghum crackers using the dryer in various drying air velocities. This drying air velocity was conducted at 0.0176; 0.0194 and 0.0272m 3 /s. The higher drying air velocity blown into the dryer through pipes above the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Rehydration reduced with an increase in drying temperature, and Verma model was the most suitable model for the compliance of experimental data. Studying the drying characteristics of sorghum crackers dried in a tray dryer, Susanti et al [28] reported that Newton and Lewis models properly fit to estimate the moisture content of the samples at different air velocities.…”
Section: Resultsmentioning
confidence: 99%
“…Rehydration reduced with an increase in drying temperature, and Verma model was the most suitable model for the compliance of experimental data. Studying the drying characteristics of sorghum crackers dried in a tray dryer, Susanti et al [28] reported that Newton and Lewis models properly fit to estimate the moisture content of the samples at different air velocities.…”
Section: Resultsmentioning
confidence: 99%
“…Selama periode laju pengeringan konstan, air permukaan pada bahan diuapkan ke lingkungan sehingga kadar air menurun dengan laju konstan. Model matematis yang menyatakan laju pengeringan konstan dinyatakan dalam persamaan berikut (Susanti et al 2016;Susanti et al 2021):…”
Section: Metodologiunclassified
“…Hal ini menunjukkan bahwa sirkulasi udara pengeringan dapat mendistribusikan energi panas dan menguapkan air pada bahan. Hal ini sesuai dengan penelitian yang dilakukan Susanti et al (2016) yang melakukan pengeringan kerupuk sorgum pada alat pengering tipe hybrid, nilai laju pengeringan pada setiap rak tidak berbeda jauh. Gambar 6.…”
Section: Metodologiunclassified
“…The drying process of kerupuk was conducted in a Memmert U30 oven (Memmert, Germany) (220V, 50/60Hz, 1400 W) whose operating conditions were 88% relative humidity (RH) inside the oven, a temperature of 50, 60 and 70°C, an air circulated system, room temperature of 27.5-31.6°C with 60-64 % RH outside. The temperature variance of 50, 60 and 70°C were chosen due to the temperature around 60°C being a suitable temperature for drying the cracker in order for there to be enough moisture available allowing for its expansion during the frying process (Susanti et al 2016). 4.5 g of wet kerupuk was placed in tray then dried in the oven.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Ovens applied in the home industry would avoid the losses by product deterioration and speed up the production process (Susanti et al 2016). The moisture content of the cracker's slice is a key quality in the drying process (Lertworasirikul 2008).…”
mentioning
confidence: 99%